1999
DOI: 10.1063/1.480241
|View full text |Cite
|
Sign up to set email alerts
|

Core-softened potentials and the anomalous properties of water

Abstract: We study the phase diagram of a system of spherical particles interacting in three dimensions through a potential consisting of a strict hard core plus a linear repulsive shoulder at larger distances. The phase diagram (obtained numerically, and analytically in a limiting case) shows anomalous properties that are similar to those observed in water. Specifically, we find maxima of density and isothermal compressibility as a function of temperature, melting with volume contraction, and multiple stable crystallin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
292
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(304 citation statements)
references
References 32 publications
11
292
0
1
Order By: Relevance
“…Two of the models (the TIP5P [45] and the ST2 [46]) treat water as a multiple site rigid body, interacting via electrostatic site-site interactions complemented by a Lennard-Jones potential. The third model is the spherical ''two-scale'' Jagla potential with attractive and repulsive ramps which has been studied in the context of liquid-liquid phase transitions and liquid anomalies [21,[30][31][32]47,48]. For all three models, Xu et al evaluated the loci of maxima of the relevant response functions, compressibility and specific heat, which coincide close to the critical point and give rise to the Widom line.…”
Section: Results For Bulk Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the models (the TIP5P [45] and the ST2 [46]) treat water as a multiple site rigid body, interacting via electrostatic site-site interactions complemented by a Lennard-Jones potential. The third model is the spherical ''two-scale'' Jagla potential with attractive and repulsive ramps which has been studied in the context of liquid-liquid phase transitions and liquid anomalies [21,[30][31][32]47,48]. For all three models, Xu et al evaluated the loci of maxima of the relevant response functions, compressibility and specific heat, which coincide close to the critical point and give rise to the Widom line.…”
Section: Results For Bulk Watermentioning
confidence: 99%
“…Unlike other network forming materials [26], water behaves as a non-Arrhenius liquid in the experimentally accessible window [16,27,28]. Based on analogies with other network forming liquids and with the thermodynamic properties of the amorphous forms of water, it has been suggested that, at ambient pressure, liquid water should show a dynamic crossover from non-Arrhenius behavior at high T to Arrhenius behavior at low T [24,[29][30][31][32][33]. Using Adam-Gibbs theory [34], the dynamic crossover in water was related to the C max P line [22,35].…”
Section: The Widom Linementioning
confidence: 99%
“…However, this is not a new observation, except for the connection to PCM phenomenology. The extraordinary parallel in physical behavior between water and the element tellurium in their supercooled liquid states was detailed in the T m -scaled plots of volume, heat capacity, and isothermal compressibility by Kanno et al [65] in 2001, and interpreted by one of us [66] as a consequence of each liquid being characterized by two different length scales -as in the Jagla model of anomalous liquids [67,68]. There are frequent references in the PCM literature to the two different Ge coordination states that might play an equivalent role.…”
Section: Discussionmentioning
confidence: 99%
“…Although transferability 16 and reproducibility issues 17 hinder the determination of a complete panel of properties, it is still possible to extract a myriad of useful information. Examples of such isotropic potentials are repul-sive shoulder potential, 18 honeycomb potential, 19 LennardJones-Gaussian potential, 20,21 Jagla potential 22,23,24 and the continuous shouldered well (CSW) potential. 25 Methanol can be modelled with attaching a second bead to a particle with the aforementioned pair potential.…”
Section: Introductionmentioning
confidence: 99%